2017
DOI: 10.3389/fimmu.2017.01171
|View full text |Cite
|
Sign up to set email alerts
|

Iron Handling in Tumor-Associated Macrophages—Is There a New Role for Lipocalin-2?

Abstract: Carcinogenesis is a multistep process. Besides somatic mutations in tumor cells, stroma-associated immunity is a major regulator of tumor growth. Tumor cells produce and secrete diverse mediators to create a local microenvironment that supports their own survival and growth. It is becoming apparent that iron acquisition, storage, and release in tumor cells is different from healthy counterparts. It is also appreciated that macrophages in the tumor microenvironment acquire a tumor-supportive, anti-inflammatory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 150 publications
(155 reference statements)
0
34
0
Order By: Relevance
“…By contrast, estrogens are known to produce reactive oxygen species (ROS) and are implicated in cellular carcinogenesis, as chronic oxidative stress promotes cell growth, survival and the tumorigenic potential of breast cancer cells (19). In the present study, we provide an update on the recent advances in the understanding of the reduction-oxidation (redox)-related molecular signaling and imbalance in the cellular redox state in malignant transformation of endometriosis (8,(20)(21)(22)(23)(24)(25)(26)(27). The pathogenesis of the malignant transformation of endometriosis remains obscure; however, the results of several studies support the hypothesis that the redox imbalance, inflammatory/immune response, cell cycle regulation and hormone activity are the deregulated functions and act in a dynamic epigenetic network (20,22,23,24).…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, estrogens are known to produce reactive oxygen species (ROS) and are implicated in cellular carcinogenesis, as chronic oxidative stress promotes cell growth, survival and the tumorigenic potential of breast cancer cells (19). In the present study, we provide an update on the recent advances in the understanding of the reduction-oxidation (redox)-related molecular signaling and imbalance in the cellular redox state in malignant transformation of endometriosis (8,(20)(21)(22)(23)(24)(25)(26)(27). The pathogenesis of the malignant transformation of endometriosis remains obscure; however, the results of several studies support the hypothesis that the redox imbalance, inflammatory/immune response, cell cycle regulation and hormone activity are the deregulated functions and act in a dynamic epigenetic network (20,22,23,24).…”
Section: Resultsmentioning
confidence: 99%
“…7c ). Sporadic evidence for this hypothesis has been obtained from cancer studies (reviewed in [ 10 ]), but systemic studies investigating the role of apo- versus holo-Lcn2 in renal epithelial regeneration following various insults would be desirable. On the other hand, it is interesting to note that we have previously obtained evidence that siderophore Fe 3+ -loaded human holo-LCN2 binds with lower affinity to the N-terminus of human LCN2-R than apo-LCN2 [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated that apo-Lcn2 induces apoptosis in Lcn2-R expressing cells [ 8 , 9 ], whereas holo-Lcn2 is anti-apoptotic and may even promote cell proliferation, e.g. in cancer cells [ 10 ]. Lcn2 is expressed in cells as a non-glycosylated ~22-kDa precursor and a glycosylated ~25-kDa mature Lcn2, but only the latter is secreted [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tumor‐associated macrophages (TAMs), which considered as a M2‐like phenotype, also contribute to carcinogenesis, particularly angiogenesis, metastasis, and suppression of antitumor responses . Indeed, TAM causes high ferroportin‐mediated iron release that provides higher iron availability in the tumor microenvironment . TAM stabilizes HIF and trigger expression of chemokines and chemokine receptors like CXCL12 and CXCR4 as well as vascular endothelial growth factor (VEGF) .…”
Section: Iron Metabolism and Immune Response To Tumormentioning
confidence: 99%
“…Moreover, TAM restrict an antitumor immune response through recruitment of immunosuppressive lymphocytes such as regulatory T cells to subvert tumoricidal lymphocyte function . Increased expression of Lipocalin‐2 (LCN‐2) was also found in TAM, which is thought to support tumor cell proliferation . Secreted LCN‐2 traffic iron through LCN2 receptor to the tumor cells can lead to increased LIP, thereby inducing antiapoptotic mediator Bcl‐2 .…”
Section: Iron Metabolism and Immune Response To Tumormentioning
confidence: 99%